Análise dos trabalhos de conclusão de curso da licenciatura integrada em ciências matemática e linguagens/UFPA - SILVA, Gediane Pereira da (2020)
This is an analysis of the 78 Course Completion Papers (TCC) produced in the Integrated Degree in Science, Mathematics and Languages from 2014 to 2018, as a way to draw a profile of the research developed by the students of the course, focused on the base knowledge fields contemplated in the curricular pedagogical project of the course. This is a research with qualitative approach of bibliographic nature, being analyzed with the content analysis approach. First we identified the type of work presented as TCC, which may be monograph, scientific paper or memorial, which showed a growing trend of development of scientific paper, later classify the works according to the thematic axes that make up the curriculum design of the course. It was possible to perceive a quantitative balance of works between the themes addressed.